2015
DOI: 10.1016/j.exppara.2014.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Target validation of the inosine monophosphate dehydrogenase (IMPDH) gene in Cryptosporidium using Phylomer® peptides

Abstract: • Yielded a relatively high functional hit rate (~17% i.e. 2/12 Phylomer ® peptides tested).• Successfully shown that TAT can deliver therapeutic Phylomer cargoes inside cells.• Opens up new therapeutic opportunities. Cryptosporidiosis, a gastroenteric disease characterised mainly by diarrheal illnesses in humans and mammals is caused by infection with the protozoan parasite Cryptosporidium. Treatment options for cryptosporidiosis are limited, with the current therapeutic nitazoxanide, only partly efficacious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…To date, the best studied drug target is the bacterial‐derived inosine 5′‐monophosphate dehydrogenase (IMPDH) gene, as Cryptosporidium does not contain guanine salvage enzymes and is totally dependent on this enzyme to convert adenosine salvaged from the host into guanine nucleotides . This coupled with the parasite's high metabolic demand for nucleotides due to the complicated life cycle of this parasite make IMPDH an important drug target …”
Section: Detection Diagnosis and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the best studied drug target is the bacterial‐derived inosine 5′‐monophosphate dehydrogenase (IMPDH) gene, as Cryptosporidium does not contain guanine salvage enzymes and is totally dependent on this enzyme to convert adenosine salvaged from the host into guanine nucleotides . This coupled with the parasite's high metabolic demand for nucleotides due to the complicated life cycle of this parasite make IMPDH an important drug target …”
Section: Detection Diagnosis and Treatmentmentioning
confidence: 99%
“…[73][74][75][76] This coupled with the parasite's high metabolic demand for nucleotides due to the complicated life cycle of this parasite make IMPDH an important drug target. [77][78][79][80][81][82][83][84][85] Other drug targets include long-chain fatty acyl-coenzyme A synthetases (LC-ACS), which are essential in fatty acid metabolism, 68 and a recent study reported good efficacy of the ACS inhibitor triacsin C against cryptosporidial infection in mice. 86 A parasite cysteine protease inhibitor was also effective in vitro and in an animal model.…”
Section: Detection Diagnosis and Treatmentmentioning
confidence: 99%
“…Another study investigated the use of Phylomer ® peptides to inhibit Cp IMPDH functions. These studies were conducted in vitro and identified two out of twelve peptides with anti-cryptosporidium functions [59]. …”
Section: The Way Forwardmentioning
confidence: 99%
“…As an alternative strategy to conventional hit identification and lead optimization of small “drug-like” molecules, peptides have been explored as IMPDH inhibitors. In particular, phylomer peptides, which represent naturally stable protein segments from phylogenetically diverse bacterial genomes with an evolutionarily optimized ability to bind protein surfaces ( Watt, 2009 ), have been screened for inhibitory activity against C. parvum IMPDH ( Jefferies et al, 2015 ). Peptides that interact with IMPDH were identified in a yeast two hybrid screen, and then tested for parasite inhibition in vitro .…”
Section: Cryptosporidiummentioning
confidence: 99%
“…Peptides that interact with IMPDH were identified in a yeast two hybrid screen, and then tested for parasite inhibition in vitro . The best peptides suppressed C. parvum growth with 50% efficiency at 8–46 μM, but had only negligible cytotoxicity in human cells ( Jefferies et al, 2015 ). Although the in vivo efficacy of these peptides remains to be established, the data underline that IMPDH is a valid pharmacological target for parasite inhibition.…”
Section: Cryptosporidiummentioning
confidence: 99%